Solve -9*v - 15 = -5*u - 4*v, -5 = v for u.
-2
Solve -3*b - 8 = -2*n, -b - 5 = -2*n - n for b.
-2
Solve -3*i + 8 = 2*s, -6*i - 4*s + 10 = -3*i for i.
2
Solve -10 = -2*r - 2*m, 7 = -r + 2*m - 0 for r.
1
Solve 11*u + 39 = 5*h + 15*u, 3*h - 27 = -3*u for h.
3
Solve 5*j + v - 19 = -3, 5*j + 4*v - 4 = 0 for j.
4
Solve -2*r + 6*r + 8 = 4*o, 3*o - 15 = 0 for r.
3
Solve 4*z - 40 = -4*q, 22 = z + 3*q + 2 for z.
5
Solve -d - 20 = 4*j, 2*j = 4*d - 177 + 167 for j.
-5
Solve 2*s + 62*i - 63*i + 7 = 0, 5*i + 25 = -5*s for s.
-4